Analisis Implementasi Manajemen Perubahan dalam Penguatan Pendidikan Karakter di Dinas Pendidikan Kabupaten Nias Barat (Lembaga Pengembangan Kinerja Dosen, 2025)
Change management plays a strategic role in strengthening character education within the West Nias Regency Education Office. This study aims to analyze the implementation of change management in strengthening character education and identify supporting and inhibiting factors in its implementation. This study used a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. Data analysis was conducted based on data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of change management was carried out in a planned manner through the formation of work teams, the active involvement of principals and teachers, and the leadership of the Head of the Office who encouraged collaboration across work units. The results of the study indicate that the implementation of change management was carried out in a planned manner and has taken place through a structured process, including the planning, implementation, and evaluation stages. This is evidenced by the formation of work teams, the active involvement of principals and teachers, and the leadership of the Head of the Education Office who encouraged collaboration across work units. The positive impact of this implementation is evident in the increase in student discipline and teacher enthusiasm in integrating character values into learning activities. Supporting factors include leadership commitment, structural support from education officials, the use of educational technology such as Smart School and Education Report Cards, and open communication. Meanwhile, obstacles faced include limited facilities, low technological literacy in some areas, and teachers' perceptions of additional workload. This study recommends strengthening technology-based training, equitable distribution of planning documents, and regular monitoring to ensure program sustainability. These findings are expected to provide input in designing more adaptive change management policies to support student character at the education unit level.